Kerala society and politics : a souvenir of the thirty-first Indian Political Science Conference held at Trivandrum in December 1969 - Sukumaran Nayar, V. K. (V. K. Sukumaran Nayar on behalf of the Reception Committee, 31st Indian Political Science Conference, 1969)
Comprises scholarly articles.